In vitro translation of human placental pregnancy-specific beta1-glycoprotein (SP1) - W. Hirunyavasit (2018)
Synthesis of SP1-glycoprotein by the human placenta was directly demonstrated, by in vitro translation of RNA extracted from full term and from early placentas in a cell-free wheat germ system followed by specific immunoprecipitation of the radioactively labeled nascent peptides. De novo synthesized SP1-glycoprotein in both RNA preparations accounted for 1-1.3% of total protein synthesis. © 1983 Birkhäuser Verlag.